Antioxidant and color properties of black soybean tempe beverage with the addition of sappan wood and cinnamon - Silviandari, Putri Masitha; Rahayu, Wahidah Mahanani; Silvana, Ana (Universitas Ahmad Dahlan, 2024)
Black soybean was fermented into Tempe to increase its functional properties and bioavailability. To develop black soybean tempe into a beverage for practical consumption, sappan wood and cinnamon were added to improve the appearance and functional properties. This research aims to determine the effect of sappan wood and cinnamon addition on antioxidant levels, phenolic levels, and brightness levels of black soybean tempe beverages. The research used a Completely Randomized Design (CRD) with a ratio of sappan wood and cinnamon at 0:0, 3:0.5, 2.5:1, and 2:1.5 (%w/w). Beverage made from commercial yellow soybean tempe was used as control. This research started by making tempe using Yogyakarta's traditional method. Beans were dehulled, boiled for 30 minutes, soaked in boiling water for 36 hours, boiled again for 30 minutes, inoculated with RAPRIMA, and incubated for 40 hours at room temperature. Tempe beverage was made by milling tempe and 80°C water at 1:3 (w/w) and the barks at the mentioned ratio, followed by filtration. The beverages were then analyzed for their Ascorbic Acid Equivalent Antioxidant Capacity (AEAC), total phenolics using the Folin-Ciocalteu method, and brightness levels using the CIE method. The results showed the antioxidant properties ranged between 82.67-86.93 mg AEAC/ml, total phenolics: 53.43-66.53 mg GAE/ml, color brightness parameter L*: 33.82-34.49, a *: 1.97-2.01, and b*: 4.09-5.05. It can be concluded that adding sappan wood and cinnamon improved the antioxidant levels and appearance of black soybean tempe beverages. The highest antioxidant properties and brightness level were obtained by adding 3% and 0.5% of sappan wood and cinnamon bark, respectively.